Effectiveness of the Flipped Classroom Model on the Problem-Solving Abilities of Science Education Students: A Meta-analysis Study - Tomi Apra Santosa; Dian Purnama Ilahi; Lisa Utami; Festiyed Festiyed; Desnita Desnita; Asrizal Asrizal; Skunda Diliarosta; Yerimadesi Yerimadesi; Fitri Arsih (Jurnal Penelitian Pendidikan IPA, 2023)
A concise the purpose of the study was to determine the effectiveness of the flipped classroom model on the problem solving skills of science education students. A total of 950 studies were analyzed obtained from six databases consisting of ScienceDirect, Education Resources Information Center (ERIC), Wiley Journal, Springer; ProQuest and IEEE aim to get relevant articles published in 2020-2023. From the analyzed studies, 21 studies were selected for meta-analysis. Data analysis with JSAP software. The results showed that the flipped classroom model provides high effectiveness on the problem solving skills of science education students (rRE = 0.97; 95 % CI [0.840; 1.111]; p < 0.001). This finding provides information for teachers to apply the flipped classroom model to improve students' problem solving skills in learning